“Punarnava” (Boerhaavia diffusa): An Ancient Herbal Medicine with the Emphasis of Ayurveda on its Therapeutic Potential - Mondal, Sumanta; Nag, Sourav; Paul, Reshmi; Panigrahi, Naresh; Roy, Partha; Revu, Baby Nalanda; Sahana, Soumitra (Current Indian Science, 2024)
A broad name for plant compounds with various structures and functions is “phytochemical.” When ingested by humans, phytochemicals may have biological activity. Plant foods, such as fruits, vegetables, whole grains, nuts, and seeds are the most prevalent sources of phytochemicals. Boerhaavia diffusa L. nom. cons. is a perennial creeping herb that grows throughout India. In the Indian medical system, it is generally referred to as “Punarnava”. In some areas of India, it is frequently used to treat jaundice. According to Ayurveda, B. diffusa is categorized as a “Rasayana” herb, which is believed to have anti-aging, disease-prevention, and life-strengthening properties. These properties are thought to significantly impact the global disease burden and the cost and accessibility of healthcare. This one is one of the first Eastern remedies that Ayurveda mentions as a possible treatment for several illnesses. Numerous ethnopharmacological reports highlight its involvement in reproductive, gastrointestinal, respiratory, urinary, hepatic/jaundice, cardiovascular, and cancer problems. Beyond that, because of the plant's therapeutic value derived from flavonoids and polyphenols, physicians and scientists should take more significant advantage of this plant to learn more about its biological and therapeutic qualities. Its taxonomy and geographic description, ethnobotanical insights, and various pharmacological characteristics were the main topics of this paper.
Keywords: Phytochemical